Impact of preoperative atrial fibrillation in patients with left ventricular assist device: A systematic review and meta‐analysis. Issue 12 (18th July 2019) - Tantrachoti, Pakpoom; Klomjit, Saranapoom; Vutthikraivit, Wasawat; Prieto, Sofia; Gongora, Enrique; Nair, Nandini
Abstract: Atrial fibrillation (AF) is a common finding in patients evaluated for left ventricular assist device (LVAD). There is conflicting data regarding the mortality risk as well as the thromboembolic risk in patients with preoperative AF who undergo LVAD implantation. We examined these risks by performing a meta‐analysis. We performed a literature search of Pubmed, EMBASE, SCOPUS, and Cochrane from inception to February 2018. The eligible studies were used to compare mortality rate and thromboembolic risk between AF and Non‐AF (NAF) groups after LVAD implantation. We obtained 391 articles from our search strategy. Seven retrospective studies were included and accounted for 5823 LVAD patients (AF 1589; NAF 4234). The median follow‐up duration ranged from 7–24 months. The pooled analysis revealed a significantly increased risk of mortality in preoperative AF patients who underwent LVAD operation compared to those with NAF (Risk Ratio [RR] 1.16, 95% CI 1.05‐1.28, I2 = 0%). Five studies reported thromboembolism events involving 1359 preoperative AF and 3893 NAF patients. The pooled analysis did not show a statistically significant association between risk of thromboembolic event and preoperative AF (Risk Ratio [RR] 1.08, 95% CI 0.86‐1.36, I2 = 76.2%). Our study shows that preoperative AF may be associated with a higher mortality rate. This study is limited by the fact that the data are pooled from retrospective studies. Further prospective studies are warranted in order to validate these results.